2019
DOI: 10.1177/1558925019867520
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of shear characteristics of woven fabrics and their interaction with fabric integrated structural factors

Abstract: Behavior of woven fabrics during complex deformations is most influentially affected by their shear behavior. Shear characteristics of woven fabrics can be explained by fabric shear rigidity and shear hysteresis. In this study, the effects of weft density, weft count, and fiber type on shear behavior of woven fabrics in the principal directions of fabric were statistically evaluated. Statistical methods such as multiple linear regression analysis, univariate test, and correlation analysis were also applied. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…The fabric tensile force and its Youngs’s modulus play a significant role in determining the fabric behavior under the punching force. Both properties define the deformation of the fabric under punching [15,17]. Results show, Figure 12, a high correlation between the fabric tensile strength and the punching force, punching energy and fabric tensile energy, punching energy and fabric Young’s modulus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fabric tensile force and its Youngs’s modulus play a significant role in determining the fabric behavior under the punching force. Both properties define the deformation of the fabric under punching [15,17]. Results show, Figure 12, a high correlation between the fabric tensile strength and the punching force, punching energy and fabric tensile energy, punching energy and fabric Young’s modulus.…”
Section: Resultsmentioning
confidence: 99%
“…However, its effect on punching energy is more noticeable. The dependency of fabric shear behavior on fabric weft density was found to be the most important factor [17,21,22]. Results confirmed that an increase in fabric weft density and weft yarn count leads to an increase in fabric shear rigidity along X and Y directions.…”
Section: Fabric Parameters Affecting Fabric Punching Forcementioning
confidence: 85%
See 2 more Smart Citations
“…Shear properties are important not only for fabrics and/or clothing but for textile composites as well. Shear characteristics of woven fabrics can be explained by two terms fabric., Shear rigidity (G) and Shear hysteresis at two angles (2HG and 2HG5) with the KESF instrument [67] . Until now, it has been known that a general empirical stress-strain curve for shear illustrates the characteristics in Fig.…”
Section: Shear Propertymentioning
confidence: 99%